The Effect of Economic Growth, Regional Own Revenue, and General Allocation Fund on Capital Expenditure in Central Sulawesi Province - Muh. Rafli Busman; Rita Yunus; Yunus Sading; Edhi Taqwa; Santi Yunus; Andi Herman Jaya; Busman Busman (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Despite the robust economic growth and rising regional income, capital expenses in Central Sulawesi are still relatively low in comparison to operational costs. This raise worries about how effective the fiscal capacity is in promoting development through public investments.  This study aims to examine the impact of Economic Growth, Regional Own Revenue (PAD), and General Allocation Fund (DAU) on Capital Expenditure across Central Sulawesi Province. The research will draw upon secondary data spanning five years (2020-2024) from the Central Statistics Agency (BPS) and BAPPEDA covering all regencies and cities within Central Sulawesi Province. The methodology follows a quantitative approach using Multiple Linear Regression Analysis with Panel Data. The investigation focuses on three independent variables - Economic Growth, Regional Own Revenue (PAD), and General Allocation Fund (DAU) and their relationship to the dependent variable of Capital Expenditure. The findings indicate that all three variables collectively contribute positively to capital expenditure, largely influenced by the highly significant PAD variable with a positive coefficient (p-value = 0.0000). Partially, economic growth and DAU are not significant despite having positive but very low coefficient values. PAD is the only factor that has a strong and beneficial effect on capital spending. This suggests that regions receiving more PAD tend to allocate more funds towards capital expenditure. The statistical analysis of the regression model in this research indicates its significance and ability to accurately explain changes in capital spending.